The role of social support in the acculturation and mental health of unaccompanied minor asylum seekers. Issue 2 (22nd January 2015) - Oppedal, Brit; Idsoe, Thormod
<x xml:space="preserve">Abstract</x> There is a lack of knowledge about psychosocial resources that may sustain post‐resettlement psychological adjustment among unaccompanied minor asylum‐seekers. The aim of this study is to investigate the impact of social support from family abroad and friends on acculturation, discrimination, and mental health among these vulnerable children and youth. Questionnaire data were collected from a population‐based multi‐ethnic sample involving 895 unaccompanied minors resettled in municipalities in all regions of the country. They met in groups in their local communities. The informants were on average 18.6 years, and had an average length of stay in Norway of 3.5 years. The findings showed that the participants suffered from high levels of ongoing war related intrusive symptoms and depression. Still, at the same time they engaged in adaptation processes that are normative to youth with immigrant backgrounds, in terms of constructing supportive networks and developing culture competence. In accordance with the main effect hypothesis, social support had direct effects on depression and indirect effects by increasing culture competence that may aid the young refugees in dealing with discrimination. However, there were no effects of social support on symptoms of PTSD. The findings give direction to areas of interventions, beyond dealing with the sequel of the traumas the unaccompanied minors have been exposed to, not only for clinicians, but also social workers and school personnel.